PREDICTIVE VALUE OF THE NEUROPSYCHOLOGICAL IMPAIRMENT SCALE IN PATIENTS WITH TRAUMATIC BRAIN INJURY - Sophia Mansouripour; Alireza Ala; Elham Afsar; Alireza Bihamta; Erfan Golshan Shali; Pouneh Hamian-roomiani; Pouya Vakilipour; Samad Shams Vahdati (İstanbul Tıp Fakültesi Dergisi)
Objective: Various studies have used different measures to predict the outcome of patients with traumatic brain injury, including the Glasgow Coma Scale (GCS), Disability Rating Scale, and length of hospital stay, among others. This study was conducted to determine the predictive significance of the Neuropsychological Impairment Scale (NIS) concerning the mortality rate, recovery, and discharge outcomes of patients who have been presented to the emergency department. Material and Method: This descriptive–analytical cross-sectional study was conducted on 100 individuals aged ≥18 years who have experienced traumatic brain injuries. A checklist was prepared incorporating items from the NIS and patient information such as age, gender, and injury mechanism details. The checklist was completed during bedside examinations. Result: The prevalence of traumatic brain injuries was higher in men (78%) in the age group of 21–40 years. The average age of patients was 41.63 years. Falling from a height was identified as the predominant cause of brain trauma, followed by twocar accidents. The mean primary GCS score was 13.47 for men and 14.63 for women. Hospitalization occurred in 67% of cases, followed by discharge in 30% and surgical intervention in 3% of cases. An inverse correlation was observed between the examined sample’s NIS standard score and the initial GCS score. Conclusion: An inverse relationship between NIS and initial GCS scores suggests that lower NIS scores are associated with better outcomes, indicating its utility as a predictive factor.